Attenuation of Visceral and Somatic Nociception by Ghrelin Mimetics - N Mohammadi E; Louwies T; Pietra C; Northrup SR; Greenwood-Van Meerveld B (Dove Medical Press, 2020)
Ehsan N Mohammadi,1 Tijs Louwies,1 Claudio Pietra,2 S Robert Northrup,3 Beverley Greenwood-Van Meerveld1 1Oklahoma Center for Neuroscience, Department of Physiology, University of Oklahoma Health Science Center, Oklahoma City, OK, USA; 2Helsinn Healthcare SA, Lugano 6915, Switzerland; 3Helsinn Therapeutics Inc., Iselin, NJ 08830, USACorrespondence: Beverley Greenwood-Van MeerveldOklahoma Center for Neuroscience, Department of Physiology, University of Oklahoma Health Science Center, O’Donoghue Building, Room 332, 1122 NE 13 th Street, Oklahoma City, OK 73117, USATel +1 405 456-3547Email Beverley-Greenwood@ouhsc.eduPurpose: The anti-nociceptive properties of ghrelin have been demonstrated in alleviating inflammatory and neuropathic pain. Whether a ghrelin receptor-mediated mechanism attenuates visceral and somatic pain in the absence of active inflammation remains to be explored. Here, we investigate the efficacy of peripherally restricted (ipamorelin) and a globally active (HM01) selective ghrelin receptor agonist in an experimental model of non-inflammatory visceral hypersensitivity and somatic mechanical allodynia.Materials and Methods: Visceral hypersensitivity was induced by dilute acetic acid (0.6%) infusion in the colon of rats in the absence of colonic epithelial inflammation. Ghrelin mimetics HM01 and ipamorelin were administered orally or intravenously, respectively. The ghrelin receptor antagonist H0900 was administered orally. Colonic sensitivity was assessed via a visceromotor behavioral response (VMR) quantified as the number of abdominal contractions in response to graded isobaric pressures (0– 60 mmHg) of colorectal distension (CRD). Somatic mechanical allodynia was quantified by the number of ipsilateral paw withdrawals in response to a calibrated von Frey filament.Results: Compared to vehicle controls, ghrelin mimetics HM01 and ipamorelin significantly attenuated colonic hypersensitivity and somatic allodynia. The anti-nociceptive effects of the ghrelin mimetics were blocked after administration of the ghrelin receptor antagonist H0900.Conclusion: We have shown that ghrelin receptor-mediated mechanisms are involved in visceral and somatic hypersensitivity in the absence of active colonic inflammation. Furthermore, visceral and somatic hypersensitivity could be attenuated by a peripherally restricted ghrelin mimetic. These results highlight a potential novel approach for treating acute visceral and somatic pain by ghrelin mimetics.Keywords: ghrelin mimetics, HM01, ipamorelin, rat, visceral hypersensitivity, somatic allodynia